Pengaruh kinerja lingkungan dan pengungkapan akuntansi karbon terhadap profitabilitas - Mariyah, Siti; Paramita, Mahardian Hersanti; Huliawati, Riska; Haryadi, Haryadi; Rahayu, Sri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study is to determine the impact of environmental performance and disclosure of carbon accounting on the profitability of manufacturing companies listed on the Indonesia Stock Exchange in 2021. In this study, the method used was an explanatory quantitative method. The sample selection technique was determined using a purposive sampling technique. The sample selected for this study was 65 manufacturing companies. The findings reveal that while carbon accounting disclosures have no impact on profitability, environmental performance has a beneficial impact on profitability (ROA). This shows that before making investment decisions, investors have considered the credibility of environmental performance but have not considered the disclosure of carbon accounting in the annual report.